CLINICAL AND MORPHOLOGICAL ASPECTS OF COMPLEX TREATMENT OF GENERALIZED PERIODONTITIS - Savchuk, O.V.; Нasіuk, N.V.; Klytynska, O.V.; Yeroshenko, G.A.; Zaliznyak, M.S. (World of Medicine and Biology, 2020)
The article presents scientific data on the substantiation of clinical effectiveness of the effectiveness of the use of the drug “Jen-metrohelur” in the complex treatment of generalized periodontitis. Thus, according to our clinical and morphological studies, the use of “Jen-metrohelur” in the treatment of generalized periodontitis is clinically effective. The justification for this provision is the results of complex clinical and morphological observations, positive dynamics of changes in PMA index (49.32 ± 1.98) and periodontal Russell index (3,89±0,54) and changes in the functional status of segmental leukocytes in the dynamics of treatment. So, according to the results of our clinical and morphological studies, the use of the medication “Jen-metrohelur” in the treatment of generalized periodontitis is clinically effective. This provision suggests that in the generalized periodontitis, cells of the inflammatory process together with disorganized cells of the epithelium, connective tissue of the gums and periodontium and bacteria form specific kinds of infiltrates in the periodontal tissues, the nature of these infiltrate initiates the incidence of relapses in the generalized periodontitis in patients.
Keywords: generalized periodontitis; gums; periodontal pockets; cells